Muslimat NU Medan and Digital Transformation: Strategic Responses to Emerging Challenges - Nur Laila Harahap; Muhammad Habibi Siregar (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
This study aims to analyze the digital adaptation strategies implemented by Muslimat NU in Medan City. The rapid advancement of digital technology has transformed communication patterns in society, compelling religious organizations to adapt while maintaining moderate Islamic values. Using a qualitative descriptive approach, data were collected through in-depth interviews, observations, and documentation involving administrators and members of Muslimat NU Medan, selected through purposive sampling. The findings indicate three main strategies: the utilization of social media as a medium for da’wah and organizational communication, the enhancement of members’ digital literacy, and intergenerational collaboration in managing digital platforms. Several challenges were identified, including limited digital literacy among members, human resource constraints, and suboptimal content management. Despite these obstacles, digital media has proven effective in strengthening organizational communication, expanding the reach of da’wah, and supporting cadre development. The contribution of this study lies in its focus on Islamic women’s organizations in non-NU stronghold regions, particularly Medan City, which presents distinct socio-religious characteristics compared to NU-based areas in Indonesia. These insights highlight how Muslimat NU navigates digital transformation while preserving cultural and religious identity, offering valuable implications for the broader discourse on religious organizations and digital adaptation.